The Use of Concrete Media in Science Learning in Inquiry to Improve Science Process Skills for Simple Machine subject - Muhamad Taufik Bintang Kejora (MUDARRISA: Jurnal Kajian Pendidikan Islam, 2020)
This study aims to determine the improvement of science process skills with the media using concrete in science learning by inquiry.  The study was conducted using a quasi-experimental design with a nonequivalent control group design.  In the experimental group applied to learn to utilize concrete media in learning science in an inquiry, while the control class applied to conventional learning utilizing audio-visual media. Subject: The study included 60 students of class V Elementary School performances in Purwakarta district. The test results for the normalization gain skills enhancement process gain values obtained experimental class (N-gain 0.46) is greater than the value of the class gain control (N-gain 0.17).  Based on the test results mean difference two improvements by using the t-test, obtained t = 2.688 table = 2.045, with sig. 0.012 α 0.05 then H0 is rejected and Ha.  Therefore, inquiry science learning by utilizing concrete media can significantly improve students' science process skills.